PENGEMBANGAN APLIKASI PENGOLAHAN DATA BARANG BUKTI DI POLRES BOYOLALI BERBASIS WEB - Pakarti, Moch. Bagoes; Budyastomo, Avin Wimar; Al Haris, Firdhaus Hari Saputro (Gaung Informatika, 2014)
Sat  Tahti (Force of Detainees and Evidence) at Polres Boyolali which has the task to manage the evidence in this case a vehicle, provide information about the vehicle seized and prepare for the service to society. Sat Tahti has provided a media that can provide information to the public but tht application is difficult to operate and there is no provided media of communication between the user. So it is  necessary  to  develop  the  ease  of  operation  and  the  addition  of  the communication media between the community and police.The  methods  used  for  data  collection  is  observation,  interview,  and literature.  Analysis  of  the  data  used  is  DAD  (Data  Flow  Diagram).  The Development method is waterfall. Assessment is the method of five view.Final  results  can  be  explained  as  follows:  (1)  Simplify  Sat  Tahti  manage data evidence the vehicle. (2) Provide ease of data retrieval based on the vehicle license  plate  number  of  the  vehicle.  (3)  With  the  development  of  these applications can improve the communication between the community and police through the medium of communication provided.